A Meta‐Analytic Review of the Association Between Alienation Appraisals and Posttraumatic Stress Disorder Symptoms in Trauma‐Exposed Adults. Issue 5 (8th May 2020) - McIlveen, Rachel; Curran, David; Mitchell, Ryan; DePrince, Anne; O'Donnell, Katie; Hanna, Donncha
Abstract: Ehlers and Clark's (2000) cognitive model of posttraumatic stress disorder (PTSD) highlights the importance of negative appraisals in maintaining posttraumatic stress. Recent research suggests that alienation appraisals, defined as feeling disconnected from the self and others, mediate the association between traumatic experiences and subsequent PTSD symptoms. To our knowledge, no systematic review has yet explored the relation between alienation appraisals and PTSD symptoms in trauma‐exposed adults, despite the important clinical implications posed by this association. A systematic search of the SCOPUS, Web of Science, PsycInfo, MEDLINE, CINAHL Plus, and PILOTS databases resulted in 470 studies, nine of which met full inclusion criteria. Studies were quality‐assessed for risk of bias using the Quality Assessment Tool for Studies with Diverse Designs (QATSDD) quality assessment tool. A random‐effects meta‐analysis for the association between alienation appraisals and PTSD symptoms showed a large total effect size, r = .57, 95% CI [.46, .66], z = 8.41, p < .001. This large effect suggests that as alienation appraisals increase, PTSD symptoms increase. Although a strong positive association was found between alienation and PTSD symptoms, the mechanism of this association remains unclear. Limitations of the research included significant heterogeneity across studies and the fact that data were correlational. Future research to explore why alienation appraisals are significant in posttraumatic stress may further help to inform therapeutic approaches to targeting alienation appraisals in trauma survivors. Recommendations are made for the clinical assessment of alienation appraisals when exploring the impact of the traumatic experience on the survivor. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Una revisión meta‐analítica de la relación entre evaluaciones de alienación y síntomas de TEPT en adultos expuestos a trauma META‐ANÁLISIS DE LA ALIENACIÓN Y SÍNTOMAS DE TEPT El modelo cognitivo del trastorno de estrés traumático (TEPT) de Ehlers y Clark (2000) destaca la importancia de las valoraciones negativas en la mantención del estrés postraumático. La investigación reciente sugiere que las evaluaciones de alienación, definidas como sentirse desconectado de uno mismo y de los demás, median la asociación entre experiencias traumáticas y síntomas subsecuentes de TEPT. Según nuestro conocimiento, ninguna revisión sistemática ha explorado aun la relación entre evaluación de alienación y síntomas de TEPT en adultos expuestos a trauma, a pesar de las importantes implicaciones clínicas planteadas por esta asociación. Una búsqueda sistemática de las bases de datos de SCOPUS, Web of Science, PsychInfo, MEDLINE, CINAHL Plus y PILOTS dio como resultado 470 estudios, nueve de los cuales reunían todos los criterios de inclusión. Se evaluó la calidad de los estudios para determinar el riesgo de sesgo mediante la herramienta de evaluación Herramienta de Evaluación de la Calidad para Estudios con Diseños Diversos (Quality Assessment Tool for Studies with Diverse Designs, QATSDD en su sigla en inglés). Un meta‐análisis de efectos aleatorios para la asociación entre evaluaciones de alienación y síntomas de TEPT mostró un gran tamaño del efecto total, r = .57, IC 95% [.46, .66], z = 8.41, p .001. Este gran efecto sugiere que a medida que aumenta la evaluación de alienación aumentan los síntomas de TEPT. Aunque se encontró una fuerte asociación positiva entre alienación y síntomas de TEPT, el mecanismo de esta asociación sigue siendo poco claro. Las limitaciones de la investigación incluyeron una heterogeneidad significativa entre los estudios y el hecho de que los datos fueron correlacionales. Las investigaciones futuras para explorar por qué las evaluaciones de alienación son significativas en el estrés postraumático puede ayudar aun más en los enfoques terapéuticos para trabajar las evaluaciones de alienación en los sobrevivientes de trauma. Se hacen recomendaciones para la evaluación clínica de las evaluaciones de alienación al explorar el impacto de la experiencia traumática en el sobreviviente. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐19‐0052.R3 Mcllveen A meta‐analytic review of the relationship between alienation appraisals and PTSD symptoms in trauma‐exposed adults Traditional Chinese 標題: 受創成人中, 疏離評價跟PTSD症狀的關連的回顧性元分析 撮要: Ehlers與Clark(2000) 的創傷後壓力症(PTSD)認知模型, 凸顯了負面評價在維持創傷後壓力所擔當的重要角色。近期有研究指, 疏離評價──即感覺自己脫離了與他人的關連, 對創傷經歷跟隨後的PTSD症狀的關連有中介作用。以我們所知, 目前仍未有系統性回顧檢視受創成人當中疏離評價跟PTSD症狀的關連, 即使這種關連已反映有重要的臨床意味。我們於SCOPUS、Web of Science、PsycInfo、MEDLINE、CINAHL Plus、PILOTS的數據庫進行系統性搜尋, 找到470份研究文獻, 當中九個符合我們的檢視範疇。我們對這些研究進行質性評估, 採用多樣化設計研究質量評估工具(QATSDD), 檢視這些研究的偏差風險。我們對疏離評價跟PTSD症狀的關連進行隨機效應元分析, 其顯示總效應量大 (r = .57, 95% CI [.46, .66], z = 8.41, p < .001) 。這反映疏離評價越多, PTSD症狀就越多。雖然疏離跟PTSD症狀有強大的正向關連, 但關連的機制仍為未知。本研究的限制, 包括不同的研究之間存在顯著的異質性, 而且數據都互為相關。未來如有研究探討疏離評價為何顯著可見於創傷後壓力, 將可進一步幫助發展出針對創傷生還者其疏離評價的療法。有關臨床為檢視生還者的創傷經歷影響而作的疏離評價評估, 我們亦作出建議。 Simplified Chinese 标题: 受创成人中, 疏离评价跟PTSD症状的关连的回顾性元分析 撮要: Ehlers与Clark(2000) 的创伤后压力症(PTSD)认知模型, 凸显了负面评价在维持创伤后压力所担当的重要角色。近期有研究指, 疏离评价──即感觉自己脱离了与他人的关连, 对创伤经历跟随后的PTSD症状的关连有中介作用。以我们所知, 目前仍未有系统性回顾检视受创成人当中疏离评价跟PTSD症状的关连, 即使这种关连已反映有重要的临床意味。我们于SCOPUS、Web of Science、PsycInfo、MEDLINE、CINAHL Plus、PILOTS的数据库进行系统性搜寻, 找到470份研究文献, 当中九个符合我们的检视范畴。我们对这些研究进行质性评估, 采用多样化设计研究质量评估工具(QATSDD), 检视这些研究的偏差风险。我们对疏离评价跟PTSD症状的关连进行随机效应元分析, 其显示总效应量大 (r = .57, 95% CI [.46, .66], z = 8.41, p < .001) 。这反映疏离评价越多, PTSD症状就越多。虽然疏离跟PTSD症状有强大的正向关连, 但关连的机制仍为未知。本研究的限制, 包括不同的研究之间存在显著的异质性, 而且数据都互为相关。未来如有研究探讨疏离评价为何显著可见于创伤后压力, 将可进一步帮助发展出针对创伤生还者其疏离评价的疗法。有关临床为检视生还者的创伤经历影响而作的疏离评价评估, 我们亦作出建议。